Cytokinin receptor antagonists derived from 6-benzylaminopurine - Nisler, Jaroslav; Zatloukal, Marek; Popa, Igor; Dolezal, Karel; Strnad, Miroslav; Spíchal, Lukás (Phytochemistry, 2010)
Recently we reported 6-(2-hydroxy-3-methylbenzylamino)purine (PI-55) as the first molecule to antagonize cytokinin activity at the receptor level. Here we report the synthesis and in vitro biological testing of eleven BAP derivatives substituted in the benzyl ring and in the C2, N7 and N9 positions of the purine moiety. The ability of the compounds to interact with Arabidopsis cytokinin receptors AHK3 and CRE1/AHK4 was tested in bacterial receptor and in live-cell binding assays, and in an Arabidopsis ARR5:GUS (Arabidopsis response regulator 5) reporter gene assay. Cytokinin activity of the compounds was determined in classical cytokinin biotests (tobacco callus, wheat leaf senescence and Amaranthus bioassays). 6-(2,5-Dihydroxybenzylamino)purine (LGR-991) was identified as a cytokinin receptor antagonist. At the molecular level LGR-991 blocks the cytokinin receptor CRE1/AHK4 with the same potency as PI-55. Moreover, LGR-991 acts as a competitive inhibitor of AHK3, and importantly shows reduced agonistic effects in comparison to PI-55 in the ARR5:GUS reporter gene assay and in cytokinin bioassays. LGR-991 causes more rapid germination of Arabidopsis seeds and increases hypocotyl length of dark-grown seedlings, which are characteristics of plants with a reduced cytokinin status. LGR-991 exhibits a structural motive that might lead to preparation of cytokinin antagonists with a broader specificity and reduced agonistic properties.
Keywords: puriny; Cytokinins; cytokininy; Biological Assay; Benzyl Compounds; biotest; Kinetin; benzylové sloučeniny; receptory buněčného povrchu; Mass Spectrometry; hmotnostní spektrometrie; kinetin; Arabidopsis; Receptors, Cell Surface; Purines